2022
DOI: 10.1111/jgh.16038
|View full text |Cite
|
Sign up to set email alerts
|

Clustering using unsupervised machine learning to stratify the risk of immune‐related liver injury

Abstract: Background and Aim: Immune-related liver injury (liver-irAE) is a clinical problem with a potentially poor prognosis. Methods: We retrospectively collected clinical data from patients treated with immune checkpoint inhibitors between September 2014 and December 2021 at the Nagoya University Hospital. Using an unsupervised machine learning method, the Gaussian mixture model, to divide the cohort into clusters based on inflammatory markers, we investigated the cumulative incidence of liver-irAEs in these cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Its has also been suggested to be high in PD-1 + CTLA-4 combination therapy [14,[18][19][20]. There are also reports that a high pre-administration lymphocyte or eosinophil count is related to ICI-induced LI [21,22], but a high eosinophil count is recently considered a risk factor [20]. In addition, factors including fever after the beginning of treatment [23] and a high neutrophil-lymphocyte ratio (NLR) after treatment are considered to be related to ICI-induced LI.…”
Section: Discussionmentioning
confidence: 99%
“…Its has also been suggested to be high in PD-1 + CTLA-4 combination therapy [14,[18][19][20]. There are also reports that a high pre-administration lymphocyte or eosinophil count is related to ICI-induced LI [21,22], but a high eosinophil count is recently considered a risk factor [20]. In addition, factors including fever after the beginning of treatment [23] and a high neutrophil-lymphocyte ratio (NLR) after treatment are considered to be related to ICI-induced LI.…”
Section: Discussionmentioning
confidence: 99%
“…GMM is a powerful method that was also able to expose potential phenotypes within an observational cohort from a previous report. 37,38 GMM is a powerful tool for phenotyping patients into interpretable groups on a study-by-study basis with different analyses and factors.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our study identified a possible clinical picture that aligns with the picture engaged by clinicians when treating patients. GMM is a powerful method that was also able to expose potential phenotypes within an observational cohort from a previous report 37,38 . GMM is a powerful tool for phenotyping patients into interpretable groups on a study‐by‐study basis with different analyses and factors.…”
Section: Discussionmentioning
confidence: 99%
“…16 Previously reported risk factors for developing ICI-induced liver injury include use of anti-CTLA-4 antibody drugs, development of irAEs in other organs, sex, fever after ICI administration, complications with autoimmune liver diseases, and type of malignant tumors, but further investigation is needed. [16][17][18][19][20] When diagnosing ICI-induced liver injury, it is important to first exclude diseases that may cause liver injury other than irAEs, as with other drug-induced liver injuries, and to evaluate the pattern and severity of the injury. A liver biopsy is useful in confirming the diagnosis, determining the presence or absence of comorbid liver disease, and evaluating the severity.…”
Section: Hepatology Researchmentioning
confidence: 99%
“…Previously reported risk factors for developing ICI‐induced liver injury include use of anti‐CTLA‐4 antibody drugs, development of irAEs in other organs, sex, fever after ICI administration, complications with autoimmune liver diseases, and type of malignant tumors, but further investigation is needed 16–20 …”
Section: Introductionmentioning
confidence: 99%